Proteomic analysis of the chondrocyte cell surface - Zhang, Xiaofei (2011)
Osteoarthritis, which is characterized by the progressive degradation of articular cartilage, is one of the major challenges for medical science because of its prevalence and lack of effective therapy. Currently, many scientists are interested in the biology of chondrocytes in health and disease because they play key roles in cartilage degradation. Membrane proteins are responsible for many important biological processes but they are poorly understood. Thus, relevant analysis of membrane proteins is still deficient. Thus, this project focuses on how to extract membrane proteins from chondrocytes and identifying these membrane proteins with the help of proteomics techniques.